Characterizing storm water dispersion and dilution from small coastal streams. Issue 6 (10th June 2016) - Romero, Leonel; Siegel, David A.; McWilliams, James C.; Uchiyama, Yusuke; Jones, Charles
Abstract: Characterizing the dispersion and dilution of storm water from small coastal creeks is important for understanding the importance of land‐derived subsidies to nearby ecosystems and the management of anthropogenic pollutants. In Southern California, creek runoff is episodic, intense, and short‐lived while the plumes are buoyant, all of which make the field sampling of freshwater plumes challenging. Numerical modeling offers a viable way to characterize these systems. The dilution and dispersion of freshwater from two creeks that discharge into the Santa Barbara Channel, California is investigated using Regional Ocean Modeling System (ROMS) simulations with a horizontal resolution of 100 m. Tight coupling is found among precipitation, hydrologic discharge, wind forcing, and submesoscale flow structures which all contribute to plume evolution. During flooding, plumes are narrow and attached to the coast, due to downwelling/onshore wind forcing and intense vorticity filaments lying parallel to the shelf. As the storm passes, the winds typically shift to offshore/upwelling favorable conditions and the plume is advected offshore which enhances its dilution. Plumes reach the bottom nearshore while they form thin layers a few meters thick offshore. Dilution field of passive tracers released with the runoff is strongly anisotropic with stronger cross‐shelf gradients than along‐shelf. Dispersion analysis of statistical moments of the passive tracer distribution results in scale‐dependent diffusivities consistent with the particle‐pair analysis of Romero et al. (2013 ). Model validation, the roles of submesoscale processes, and wind forcing on plume evolution and application to ecological issues and marine resource management are discussed. Key Points: Tight coupling among precipitation, discharge, winds, and currents contribute to plume evolution Plume dilution is strongly anisotropic with stronger cross‐shelf gradients than along‐shelf Statistical dispersion analysis of runoff tracer results in scale‐dependent relative diffusivities